The red badge of courage - Crane, Stephen, 1871-1900.; Kidder, Harvey, illus (New York Golden Press, 1968)
During his service in the Civil War, a young Union soldier matures to manhood and finds peace of mind as he comes to grips with his conflicting emotions about war.
Stack Area (7-8-10)
Keywords: Chancellorsville, Battle of, Chancellorsville, Va., 1863-- Juvenile fiction; Chancellorsville (Va.), Battle of, 1863--Fiction.; United States--History--Civil War, 1861-1865--Fiction.; War stories; Historical fiction